A unified quasi-three-dimensional solution for vibration analysis of rotating pre-twisted laminated composite shell panels. (15th February 2022) - Chen, Yukun; Ye, Tiangui; Jin, Guoyong; Lee, Heow Pueh; Ma, Xianglong
Highlights: A unified quasi-3D dynamic model for rotating pre-twisted laminated composite shell panels is first presented. Initial centrifugal stresses are accurately predicted by a separate quasi-static analysis. Several typical case studies are presented to show the present model's accuracy and applicability. Parametric studies are performed on vibrations of pre-twisted laminated composite shell panels. Abstract: This study presents a unified quasi-three-dimensional (quasi-3D) solution for the free vibration analysis of rotating pre-twisted laminated composite shell panels. Based on the 3D elasticity shell theory, Carrera unified formulation is employed to reduce the complete 3D dynamic model to a hierarchical 2D dynamic model with a capacity for 3D solving accuracy. A separate quasi-static analysis is conducted to precisely acquire the centrifugal stresses that occur in the rotating laminated composite shell panels. The present quasi-3D dynamic model considers the Coriolis forces, rotational softening effect as well as prestress stiffening effect. Several case studies are presented including the rotating pre-twisted plates, pre-twisted cylindrical shell panels and untwisted conical shell panels with different lamination schemes and geometric parameters. In each case study, the vibration characteristics predicted from the present theoretical model are compared with the reported studies and those from the commercial finite element software. It indicates that the quasi-3D dynamic model has good accuracy and is appropriate for different types of rotating laminated composite shell panels. The influences of the rotating speed, pre-twisted angle, fiber orientation and subtended angle on the vibration behaviors of the rotating pre-twisted laminated composite shell panels are studied as well.